A Comparative analysis of OFDM based Communication using different Mapping Schemes for Signal Modulation - Mahmood, Nasir; Shahid, Muhammad Khalil; Saeed, Ali (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
OFDM is a multiplexing technique that is used to divide a frequency spectrum into sub-carriers that are orthogonal to each other. They are capable to carry high rate data transmission. TheÂ orthogonality is maintained by keeping one sub carrier, null on the centre of other sub carriers. Sub-carriers have cyclic prefix which is placed in between them and the bandwidth wastage due to guard band is reduced up to 50%. Spectral efficiency is ofÂ OFDM is far better than other frequency modulation techniques due to othrognality. Additionally, CP design helps in better diversity gain. The data is dispensed as sub-streams among sub carriers and each of the sub carrier is modulated as per the coding (PSK, BPSK, QAM). Thus rather modulating whole data stream over a single frequency, sub carriers are allocated portions of data that ensure large amount of data processing. To ensure orthogonality, serial data is converted into smaller parallel streams and are fed toÂ IFFT module, after which P/S conversion is performed and CP is inserted between the sub-carriers. The reverse of these steps happens in the receiving module. Important aspects ofÂ OFDM systems are, Synchronization, Pilot allocation,the Channel State Information or Channel estimation etc. However this paper takes up sub-carrier modulation techniques inÂ OFDM systems and puts a comparative analysis of them.